The political anthropology of internationalized politics - Biecker, Sarah; Schlichte, Klaus (Rowman & Littlefield, 2021)
This volume offers insights from political anthropology on how to analyze and how to think about contemporary areas of internationalized political phenomena in a fresh manner. By drawing on a variety of cases like policing, budgeting, the role of monetary politics in everyday life, development agencies, and international organisations it shows the promise of an "extended experience" for the study of international politics, yet without glossing over the limits of such approaches.